The Left Hand of God - Hoffman, Paul (Penguin Group, 2010)
They call him CALE. He is strange and secretive, witty and charming - and violent. But when he opens the wrong door at the wrong time he witnesses an act so horrible he must flee the vast and desolate Santuary of the Redeemers, or die.
Keywords: Fantasy; Juvenile Fiction